(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
This study develops a typological framework for Indian temple towns, addressing the gap in understanding their spatial organization and urban growth patterns. By analysing key spatial elements, including temple placement, street grids, and zoning of residential and commercial areas, this research explores the complex interplay between religious, cultural, and urban factors. A distinction is made between intrinsic characteristics-such as geography, history, and architecture-and extrinsic factors-like social structure, religious significance, and broader socio-economic influences. The framework reveals the challenges faced by temple towns, such as infrastructure strain, urban sprawl, and the pressures of tourism and commercialization. It emphasizes the need for nuanced urban planning that integrates cultural heritage with modern development, proposing a balanced approach to maintain the spiritual and socio-economic vitality of these towns. The study’s findings underscore the critical role of temples as catalysts for urban development and social cohesion, while also highlighting their vulnerability to rapid urbanization. The research contributes to the field by offering actionable insights for urban planners, policymakers, and cultural historians aiming to preserve the unique identity of temple towns amidst contemporary challenges. The study’s reliance on secondary sources is acknowledged, and future empirical research is recommended to refine the framework and inform policy decisions for sustainable temple town development, ensuring the preservation of both heritage and modern urban functionality.